f(x)=1x, g(x)=1x, then (f∘g)(x)

6 answers

1x is the same as x

(f∘g)(x)
= f(g(x) )
= f(x)
= x
so is g of x the inverse
did you mean f(x) and g(x) to be the same and = x ??

in that case y = x is the equation for both
and the inverse of y = x is indeed y = x
f(x)=x2−1, g(x)=2x+2, then (fg)(x)=

x2−12x+2, x≠1

so is this correct
cuz i got x ≠ -1
I assume we are doing a new question and
f(x) = x^2 - 1 , g(x) = 2x + 2

then
(fg)(x)
= f(g(x))
= f(2x + 2)
= (2x + 2)^2 - 1
= 4x^2 + 8x + 4 - 1
= 4x^2 + 8x + 3

test with some value, say x = 3
g(x) = 2(3) + 2 = 8
f(x) = x^2 - 1
f(8) = 64 - 1 = 63

f(g(3)) = 4(9) + 8(3) + 3
= 63

It is highly probable that my answer is correct